EFFECT OF SEASON ON PROXIMATE COMPOSITION AND FATTY ACIDS PROFILE OF LLAMA MEAT IN EXTENSIVE REARING - Mamani-Linares, Lindon W. (2013)
This study compared the proximate composition and fatty acids profile of llamas slaughtered in two seasons. Twenty 18-24 month old llamas reared in native pastures were used, of which 10 were slaughtered in the dry season and 10 in the rainy season under standard procedures. Carcasses were stored for 24 h in a cold room (4 to 6 ºC). Samples of the Longissimus lumborum muscle were collected and moisture, crude protein, lipids and ashes were analysed. Llama meat slaughtered in the rainy season had higher intramuscular fat content (p<0.10) and higher levels of monounsaturated and polyunsaturated fatty acids (p<0.05), but lower levels of saturated fatty acids (p<0.05) as compared to llama meat slaughtered in the dry season. The ratio polyunsaturated/saturated fatty acid ratio and linoleic conjugated content was higher in llama meat of the rainy season. However, meat of both seasons showed an n-6/n-3 ratio within recommended levels (4) and good levels of desirable fatty acids (DFA). In conclusion, the meat of young llamas of both seasons has favorable fat characteristics for consumption.